2017
DOI: 10.4067/s0718-95162017000400007
|View full text |Cite
|
Sign up to set email alerts
|

Acid tolerant Rhizobium strains contribute to increasing the yield and profitability of common bean in tropical soils

Abstract: Symbiosis of common bean with nitrogen-fixing bacteria can lead to a reduction in production costs and in environmental impacts. Considering the diversity of soils and climates, it is important to validate bacterial strains under different conditions to consolidate their recommendation as inoculants. Studies concerning the economic viability of Rhizobium inoculation in common bean are few, but they could assist in choosing the strain to be adopted. The aim of this study was to evaluate the performance of Rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
14
0
2
Order By: Relevance
“…It has in fact reported that increasing the pH of the rhizospheric soil may be an important consequence of N 2 fixation by bacteria [ 38 ]. On the other hand, Oliveira et al [ 39 ] examined five NFB bacterial strains and reported the pH of the culture medium after growth for four strains was neutral while another strain changed the pH to acidic.…”
Section: Discussionmentioning
confidence: 99%
“…It has in fact reported that increasing the pH of the rhizospheric soil may be an important consequence of N 2 fixation by bacteria [ 38 ]. On the other hand, Oliveira et al [ 39 ] examined five NFB bacterial strains and reported the pH of the culture medium after growth for four strains was neutral while another strain changed the pH to acidic.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the presuppositions of ANOVA, the data of number of nodules and nodule dry matter were first transformed in (x + 0.5) 0.5 . According to the official protocol for evaluation of viability and agronomic efficiency of strains, inoculants, and the literature (Fonseca et al, 2013;Figueiredo et al, 2016;Pádua Oliveira et al, 2017). This argument is pertinent, even though there is no dependence of the locations on the effects of the treatments on BSY.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos indicam que o fornecimento de N 2 pela simbiose de rizóbios e feijão-caupi varia de 15 a 99% da necessidade da leguminosa (NCUBE et al, 2007;NAAB;CHIMPHANGO;DAKORA 2009). Esta variação deve-se à diversidade funcional do isolados (JAISWAL; DAKORA, 2019) e boa capacidade de competição dos isolados selecionados por sítios de infecção nodular (Oliveira et al, 2017;Ferreira et al, 2019).…”
Section: Conclusõesunclassified